When The Muse Takes It All: A Model For The Experience of Timelessness in Organizations - Mainemelis, Charalampos (Academy of Management Review, 2001)
I propose a model in which I describe the way individuals experience timelessness by becoming engrossed in attractive work activities, the contextual conditions that facilitate or hinder that process, and the effects of timelessness on the creativity of organizational members. Building upon multidisciplinary perspectives, I suggest that timelessness is a constellation of four experiences: a feeling of immersion, a recognition of time distortion, a sense of mastery, and a sense of transcendence.